P006 Clinical evaluation of the resistanceplus™ mg kit, for detection of mycoplasma genitalium and screening for macrolide resistance. (8th June 2017) - Erskine, Simon; Tan, Litty; Su, Jenny; Murray, Gerald; Bradshaw, Catriona; Fairley, Christopher; Garland, Suzanne; Mokany, Elisa; Tabrizi, Sepehr
Abstract : Introduction: European guidelines on Mycoplasma genitalium (MG) infections and on the mangement of non-gonococcal urethritis strongly recommend NAAT testing for MG and screening for macrolide resistance. The ResistancePlus™ MG kit has been developed for the simultaneous detection of MG and five mutations in the 23S rRNA gene associated with azithromycin resistance. Methods: The ResistancePlus™ MG kit (SpeeDx) was evaluated in a prospective-restrospective study on 182 urogenital samples from patients routinely tested for Chlamydia and gonorrhoea. The ResistancePlus™ MG (550) kit was performed using the 7500 Fast (Applied Biosystems), after sample extraction on the MagNA Pure 96 Instrument (Roche) using the DNA and Viral NA Small Volume Kit following the Universal Pathogen 200 protocol. Results were analysed using the FastFinder ResistancePlus™ MG (7500) analysis software. Results were compared with an in-house qPCR test for MG detection with positives subsequently sequenced to determine 23S rRNA mutation status. Results: The ResistancePlus™ MG kit showed high clinical performance compared with the reference methods with sensitivity and specificity for MG detection of 98% and 100%, and 23S rRNA mutation detection of 92.5% and 100%, respectively. The ResistancePlus™ assay has an analytical sensitivity of 10-15 copies for all targets, and no cross-reactivity was seen in a wide range of non-target organisms. Discussion: The ResistancePlus™ MG kit demonstrated excellent clinical performance for the simultaneous detection of MG and mutations associated with macrolide resistance. Detection of MG with resistance information is capable of guiding personalised treatment at the first health-care visit, reducing clinical-care costs and reducing the spread of antimicrobial resistance.